Hiwalah Sebagai Instrumen Mitigasi Gagal Bayar UMKM: Model Pengalihan Piutang Berbasis Koperasi Syariah - Abid Nurhuda; Inamul Hasan Ansori; Nur Muhammad Lathif (Jurnal Ekonomi Islam, 2025)
Micro, Small, and Medium Enterprises (MSMEs) occupy a strategic position in Indonesia's economic structure, yet the financing they obtain is frequently accompanied by considerable default risk, particularly within sharia microfinance institutions and sharia cooperatives that serve as the primary source of capital for lower- and middle-tier business actors. This condition calls for a risk mitigation instrument that is not only commercially effective but also compliant with sharia principles, given that conventional collection approaches often conflict with muamalah ethics. This paper aims to formulate a conceptual model of receivables transfer based on the hiwalah al-haq contract as an instrument for mitigating MSME default risk within sharia cooperatives. The method employed is qualitative, using a literature study approach that examines the foundations of fiqh muamalah, fatwas of the National Sharia Council-Indonesian Ulama Council (DSN-MUI), and contemporary practices of the hiwalah contract in sharia financial institutions. The findings indicate that hiwalah al-haq can be adapted into a model for transferring collection rights from MSMEs facing payment difficulties to sharia cooperatives acting as muhal 'alaih, which then carry out collection professionally in exchange for a fixed ujrah, thereby avoiding riba and gharar practices commonly found in conventional factoring schemes. This model simultaneously realizes maqashid al-sharia in the form of property protection (hifdz al-mal) without compromising the dignity of debtors experiencing hardship.